(untitled) (Revista Contexto & Saúde, 2022)
Adolescents make a target group for frequent advertising and a high prevalence of self-medication. This paper aims to outline the profile of medication use by high school students in a public school in Rio de Janeiro. A cross-sectional study was carried out with a semi-structured questionnaire regarding the use of medications. The results show that 31.90% of the students used it regularly, while 77.16% used some medication in the 15 days prior to the research, with the most mentioned drugs being dipyrone, Dorflexâ and contraceptives. The use of medicines was related to the female gender, medical appointments in the last year and to other healthcare professionals. The use in the previous 15 days was also related to self-medication, a practice whose regular frequency was reported by 17.67% of students mainly for pain relief (63.09%), allergy (17.35%) and tension and stress relief (10.41%). The high percentage of medication use and self-medication reinforce the relevance of health education and the promotion of rational drug use in schools.